2016
DOI: 10.1111/echo.13249
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Lung Ultrasound B‐Lines for Detection of Lung Radio‐Induced Toxicity in Breast Cancer Patients after Radiation Therapy

Abstract: Among women receiving radiotherapy after breast cancer, B-lines are present predominantly in the irradiated lung. These data suggest that B-lines by LUS could provide, at a subclinical stage, a radiation-free biomarker of radiotherapy-induced lung damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In the treatment of breast with VMAT, the dose distribution to the lungs is normally grossly different from what is achieved with the conformal tangential beams. In a recent report, Petruzzelli et al 21 evaluated the number of B-lines in lung ultrasound examination (I lung and C lung ) on patients treated for breast cancer. Authors found a significantly larger amount of B-lines in the I lung ; in particular, the pattern was mainly in the anterior rather than the posterior chest, i.e.…”
Section: 10mentioning
confidence: 99%
“…In the treatment of breast with VMAT, the dose distribution to the lungs is normally grossly different from what is achieved with the conformal tangential beams. In a recent report, Petruzzelli et al 21 evaluated the number of B-lines in lung ultrasound examination (I lung and C lung ) on patients treated for breast cancer. Authors found a significantly larger amount of B-lines in the I lung ; in particular, the pattern was mainly in the anterior rather than the posterior chest, i.e.…”
Section: 10mentioning
confidence: 99%
“…The B-lines are vertical hyperechoic lines, which emanate from the pleural line, move with the breathing cycle, erase the A-lines, and extend to the viewing screen's lower limit (Figure 2B). The finding of three or more B-lines between two ribs indicates interstitial pulmonary syndrome, such as pulmonary congestion 8,9 . The comet tail is a short reverberation artifact, hyperechoic, move with lung sliding, whose appearance is obviously different from B-lines and can be seen in normal lungs 10,11 .…”
Section: Lung Artifactsmentioning
confidence: 99%
“…[18][19][20] B lines and other artifacts may be present in association with lung or pleural modifications in many interstitial lung diseases and other diffuse parenchymal lung diseases, including idiopathic pulmonary fibrosis (IPF), systemic sclerosis, interstitial pneumonia, rheumatoid arthritis, nephrotic syndrome, ARDS, radiation fibrosis. [21][22][23][24][25][26] As B lines are a type of reverberation artifact mainly generating when sound waves excite the fluid trapped between air bubbles causing the fluid to resonate, the number of B lines will increase in all those pathological pleuro-pulmonary conditions where the proportion of air/liquid film changed. However, despite many recent attempts of counting artefacts for the diagnosis of pulmonary fibrosis, pulmonary oedema, or any extra-vascular lung water have been proposed, these artifacts lack any disease-specificity.…”
Section: Resultsmentioning
confidence: 99%